Lutosławski's worlds - Jakelski, Lisa; Reyland, Nicholas (Boydell & Brewer Ltd., 2018)
A landmark volume which looks at the multifaceted spheres that informed the composer's life and works and represents a new departure in the study of his music. In this volume, for the first time, the world's leading Lutoslawski scholars consider the full range of his musical output and the biographical, cultural and historical contexts in which those musics were created. It contends that all of Lutoslawski's worlds are equally worthy of study, because each represents an opportunity better to understand the life and music of a figure of paramount importance to the critical and cultural history of twentieth-century music